Asuhan Keperawatan Medikal Bedah dengan Penerapan Fisioterapi Dada pada Nn.N untuk Mengurangi Jumlah Sputum terhadap Penderita Pnuemonia di Ruang Rawat Inap di RS Harapan Bunda Kota Batam Tahun 2025 - Ramadhani, Muhammad Ilham Rezki; Fatrida, Dedi (PPNI UNIMMAN, 2025)
Pneumonia is a lung infection that causes the air sacs to fill with fluid or pus. This disease can be caused by bacteria, viruses, fungi, or parasites, with varying degrees of severity depending on the cause and condition of the sufferer. Symptoms include cough, fever, and shortness of breath. Data obtained from the Batam City Health Office of pneumonia in 2023, there were 1,509 cases of pneumonia, the most cases were found in Batam City (1,182 cases), while the fewest cases were recorded in Lingga Regency (5 cases). This Professional Scientific Paper aims to provide medical-surgical nursing care with the application of chest physiotherapy to Ms. N to reduce the amount of sputum for pneumonia sufferers in the inpatient room at Harapan Bunda Hospital, Batam City in 2025. The method used in this Professional Scientific Paper is a case study conducted based on the stages of nursing care including assessment, data analysis, diagnosis, intervention, implementation, and nursing evaluation. The results showed a decrease in sputum production on the third day, a decrease in fever, and an improvement in sleep patterns. Patients are expected to understand that chest physiotherapy can reduce sputum production.